«Modification of ghosts»: conductors interpretations of Yevhen Stankovych’s Sinfonietta in 2017 and 2023 - Dyachkova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
The relevance of the study. «Sinfonietta» (1971) stands as one of the pioneering polystylistic compositions in Ukraine. This work marked the artistic debut of Yevhen Stankovych, a prominent figure in contemporary Ukrainian music, and earned him recognition. «Sinfonietta» incorporates fragments from various musical styles and compositions, each evolving independently in performance practice. It is the style and works of J. S. Bach, G. Mahler, S. Prokofiev, and I. Stravinsky. Listeners in the 1970s, 2017, and 2023 have interpreted these musical polystylistic references in diverse ways. The dynamic evolution of performing interpretations and listening perceptions of «Sinfonietta» has unfolded against the active interplay of political propaganda and musical life. The performing interpretations of "Sinfonietta" today align with the broader context of the heated discussions about Russian heritage in Ukrainian culture. The main objective of the study. The purpose of the article is to reveal the author’s (composer’s) intentions for the composing of the «Sinfonietta» in modo collage and to study the changes of semantic emphasis in the music meaning sphere in the conductor’s interpretations of this work depending on the social and media contexts in 2017 and 2023. The methodology. The work uses the methods of contextual analysis and comparative studies. The research on performance interpretations of music is based on the theory of interpretation by V. G. Moskalenko. Results and conclusions. The type of «play with other composers’ styles» in «Sinfonietta» was new, even in the context of the widespread use of stylization in Ukrainian music in the 60s and 70s. Within the text of «Sinfonietta,» the inclusion of a quote from the Second Prelude in C minor from the first volume of «The Well-Tempered Clavier» by I. S. Bach and the emulation of S. Prokofiev’s style carried profound symbolic significance. It is plausible to interpret the с-moll Prelude quote as a response to Arvo Pärt’s «Credo» (1968), which incorporated a quote from the C-dur Prelude in the first volume of the Well-Tempered Clavier — considering the political persecution faced by Arvo Pärt and the Estonian Philharmonic workers after the premiere of «Credo». Y. Stankovych’s inclusion of the prelude quote took on the nature of a social challenge — a gesture of solidarity with his Estonian counterpart. S. Prokofiev’s stylistic influence on Ukrainian musical culture during the 60s and 70s manifested itself through socially oriented, "classical" compositions by members of the «Kyiv avantgarde» group, notably V. Silvestrov. The expulsion of V. Silvestrov from the Union of Composers of Ukraine in 1970 triggered an artistic response in 1971 in «Sinfonietta» by Y. Stankovych. When Y. Stankovych presented the piece upon joining the Union of Composers, its provocative nature was evident but closed for the conservative musicians. Additional motivations for stylizing in the spirit of S. Prokofiev within the «Sinfonietta» are rooted in Y. Stankovych’s musical preferences. His interpretation of the «composer’s school» concept is especially significant. The fact that S. Prokofiev studied under R. Glier held considerable value for Y. Stankovych. Notably, the 20th-century Ukrainian music classics Levko Revutsky and Borys Lyatoshynsky were also students of Reinhold Glière. B. Lyatoshynsky mentored Y. Stankovych. In essence, the emphasis on the works of I. S. Bach, G. Mahler, S. Prokofiev, and I. Stravinsky in the «Sinfonietta» directed the listeners of the 1970s toward music that, according to the prevailing Soviet ideological standards of that era, was slated for silencing, ignoring, and, ultimately, destruction. Yet, the compositions of these composers held immense importance for Y. Stankovych. The composer valued their «freedom of spirit» and exceptional artistic professionalism. In the 1990s, Y. Stankovych delved into themes associated with the concept of national memory, evident in works such as «’Panahyda’ for those who died of hunger,» [Requiem for Holodomor victims], Kaddish-Requiem «Babyn Yar» (1991), and «Black Elegy» (1991). Subsequently, the composer’s work began to symbolize the image of national consciousness. A «vulnerability zone» appeared in the semantic field of «Sinfonietta,» with the name of S. Prokofiev, which after 2014 was associated with the symbols of Russian art. An updated semantic vision of the «Sinfonietta’s» conception distinguishes the interpretation of the Ukrainian conductor Volodymyr Sirenko. The features of this performance version [Stankovych, Sirenko, 2017] connected with strengthening elements of the Y. Stankovych author’s style. The conductor pays attention to the composer’s timbre dramaturgy, vocalization of instrumental lines, rhetoric of solo episodes, «public speech» musical images, and rhetorical exclamations. Prokofiev’s sphere in the interpretation of V. Sirenko was related to the field of musical fairy tale intonational groups and had an aggressive emotional load. The culmination of V. Sirenko’s interpretations is a tragic trombone solo. Due to the maximum detail in the articulation, it turns into a solo restrained speech of the crying hero - as a witness of tragic events. Dilyaver Osman’s interpretation [Stankovych, Osman, 2023] distinguishes the finding of new intonation parallels between the work «Sinfonietta» by I. Stravinsky, K. Debussy, F. Poulenc, K. Orff. The texture of the «Sinfonietta» strengthened the position of the quote from the prelude by I. S. Bach. The nature of the trombone solo has changed — instead of the genre model of a solo speech, the conductor uses the model of a choral funeral march. Conclusions and perspectives of the study. «Sinfonietta» by Y. Stankovych is a work that has demonstrated incredible musical images and semantic mobility during its 50 years of existence. In contemporary interpretations, it is a semantic and stylistic «transformer» capable of forming a new concept of music from small changes in intonations. The «playing with styles» demonstrated its potential as a musical «documentary narrative about the war.» Further studies of this work will likely unfold in the field of intertextual connections, both with the texts of other composers and in the inner area of the music of Y. Stankovych.